The Incidence of Breast Cancer among Disabled Kansans with Medicare - Rogers, Austin R; Lai, Sue-Min; Keighley, John; Jungk, Jessica (Kansas Journal of Medicine, 2015)
BACKGROUND: Breast cancer disparities by disability status are poorly understood. While previous studies have shown increased odds of late stage at diagnosis, it is unclear whether the incidence of breast cancer varies by disability status. METHODS: To assess cancer incidence and stage at diagnosis among disabled and nondisabled Medicare beneficiaries in Kansas, a retrospective cohort study was conducted using linked Medicare enrollment and Kansas Cancer Registry data from 2007 to 2009. Disability status was determined by the indicator for the original reason for Medicare eligibility. RESULTS: Among the 651,337 Medicare beneficiaries included in the cohort, there were 2,384 cases of breast cancer. The age-adjusted incidence was 313 per 100,000 among female beneficiaries with disabilities and 369 per 100,000 among nondisabled female beneficiaries. The adjusted incidence rate ratio was 0.93 (95% CI 0.73-1.18). When assessing stage at diagnosis, there was no difference in the odds of late stage at diagnosis by disability status (OR = 1.02; 95% CI 0.68-1.50). CONCLUSION: No significant difference in incidence or stage at diagnosis was identified among this cohort. The use of Medicare eligibility to define disability status presented a number of limitations. Future studies should seek alternate definitions of disability to assess disparities in breast cancer incidence, including definitions using Medicare claims data.